2012
DOI: 10.1371/journal.pone.0044962
|View full text |Cite
|
Sign up to set email alerts
|

Sirenomelia Phenotype in Bmp7;Shh Compound Mutants: A Novel Experimental Model for Studies of Caudal Body Malformations

Abstract: Sirenomelia is a severe congenital malformation of the lower body characterized by the fusion of the legs into a single lower limb. This striking external phenotype consistently associates severe visceral abnormalities, most commonly of the kidneys, intestine, and genitalia that generally make the condition lethal. Although the causes of sirenomelia remain unknown, clinical studies have yielded two major hypotheses: i) a primary defect in the generation of caudal mesoderm, ii) a primary vascular defect that le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 78 publications
1
23
0
1
Order By: Relevance
“…Other models of sirenomelia exhibit a reduction in T (Abu-Abed et al, 2001; Sakai et al, 2001; Zakin et al, 2005). Moreover, in sirenomelia, the medial umbilical roots are missing (Garrido-Allepuz et al, 2012; Zakin et al, 2005) without concomitant effects on cell death (Zakin et al, 2005), similar to our findings in T C /T C homozygous mutants. Clinically in humans, posterior defects encompassing the hindlimbs in the orphan disease, sirenomelia, are associated with axial misplacement of the umbilical artery to the aorta (Stevenson et al, 1986); affected individuals typically die immediately after birth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other models of sirenomelia exhibit a reduction in T (Abu-Abed et al, 2001; Sakai et al, 2001; Zakin et al, 2005). Moreover, in sirenomelia, the medial umbilical roots are missing (Garrido-Allepuz et al, 2012; Zakin et al, 2005) without concomitant effects on cell death (Zakin et al, 2005), similar to our findings in T C /T C homozygous mutants. Clinically in humans, posterior defects encompassing the hindlimbs in the orphan disease, sirenomelia, are associated with axial misplacement of the umbilical artery to the aorta (Stevenson et al, 1986); affected individuals typically die immediately after birth.…”
Section: Discussionsupporting
confidence: 89%
“…3 A, B ). As the origin of these curving branches is obscure, previous reports have referred to them as the “re-curved portions of the dorsal aortae” (Garrido-Allepuz et al, 2012; Zakin et al, 2005) or the “medial umbilical roots” (Gest and Carron, 2003). …”
Section: Resultsmentioning
confidence: 99%
“…A recent study investigated the role of BMP signaling in PCM morphogenesis using ISL1 (Islet1 transcription factor)-expressing cells that originate from the anterior PCM and appear to contribute to both dorsal and ventral GT. Loss of BMP4 in the anterior PCM also results in a sirenomelia-like phenotype which includes hindlimb fusion, lethal pelvic/urogenital aplasia, and GT hypoplasia [Garrido-Allepuz et al, 2012;Suzuki et al, 2012]. Taken together, these studies suggest that the proper morphogenesis of the PCM is essential for external genitalia development since it is speculated to be the source of the GT mesenchyme.…”
Section: Development Of the Bipotential External Genitaliamentioning
confidence: 82%
“…Next, we investigated whether the loss of FGF signaling affects other growth factor signaling activities during GT outgrowth. Previous reports have demonstrated that SHH, WNT‐β‐catenin, and bone morphogenetic protein (BMP) signaling coordinately regulate external genitalia development (Miyagawa et al, ; Lin et al, ; Seifert et al, ; Haraguchi et al, ; Lin et al, ; Garrido‐Allepuz et al, ; Suzuki et al, ; Xu et al, ). The expression of Shh and its downstream target Ptch1 (Pearse et al, ) in the GT was not significantly altered in Isl1 C re/ + ; Fgfr1 f/f ; Fgfr2 f/f embryos compared with that in the controls (Fig.…”
Section: Resultsmentioning
confidence: 99%